2019
DOI: 10.3847/1538-4357/ab06f2
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Magnetic Rayleigh–Taylor Unstable Plumes and Hybrid KH-RT Instability into a Loop-like Eruptive Prominence

Abstract: MRT-unstable plumes are observed in a loop-like eruptive prominence using Solar Dynamic Observatory/Atmospheric Imaging Assembly observations. The small-scale cavities are developed within the prominence, where perturbations trigger dark plumes (P1 and P2) propagating with speeds of 35–46 km s−1. The self-similar plume formation initially shows the growth of a linear MRT-unstable plume (P1), and thereafter the evolution of a nonlinear single-mode MRT-unstable second plume (P2). A differential emission measure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Additionally, Khomenko et al(2014a) showed that the non-ideal, partially ionized chromospheric plasma with resistive and ambipolar diffusion taken into account experiences larger growth rate of the RT instability (RTI), faster plasma flows, rapid downflows, evolution of the high temperature bubbles, and the asymmetry between large rising bubbles and small-scale down-flowing fingers, compared to the plasma evolution in the framework of ideal MHD. Such dynamical plasma processes, elevated temperatures, and RT features are well observed by Mishra and Srivastava (2019). Usually, the ideal MHD is sufficient to explain the RT instability.…”
Section: Mhd Instabilities In the Chromospheric Plasmamentioning
confidence: 82%
See 4 more Smart Citations
“…Additionally, Khomenko et al(2014a) showed that the non-ideal, partially ionized chromospheric plasma with resistive and ambipolar diffusion taken into account experiences larger growth rate of the RT instability (RTI), faster plasma flows, rapid downflows, evolution of the high temperature bubbles, and the asymmetry between large rising bubbles and small-scale down-flowing fingers, compared to the plasma evolution in the framework of ideal MHD. Such dynamical plasma processes, elevated temperatures, and RT features are well observed by Mishra and Srivastava (2019). Usually, the ideal MHD is sufficient to explain the RT instability.…”
Section: Mhd Instabilities In the Chromospheric Plasmamentioning
confidence: 82%
“…A representative evolution of RT instability in the solar prominence system, resulting from the above equation, is shown in Figure 7 both in the observations (left) and numerical modeling (right). The evolution of the bubbles and plumes are characteristic features associated with the RT instabilities evolved in the solar chromospheric prominence plasma (Berger et al 2010;Hillier et al 2012;Mishra and Srivastava 2019).…”
Section: Mhd Instabilities In the Chromospheric Plasmamentioning
confidence: 99%
See 3 more Smart Citations